Adenoma de hipófise em uma gata com hiperadrenocorticismo - Corgozinho, Katia Barão; Belchior, Cristiane; Souza, Raquel Calixto de; Leite, Juliana da Silva; Ferreira, Ana Maria Reis (Acta Scientiae Veterinariae, 2018)
Background : : : : Feline Cushing’s syndrome (FCS) is a disorder of excessive cortisol secretion by the adrenal glands and is rare in cats. The most frequently observed clinical signs are polyuria, polydipsia, and polyphagia which are also consistent with diabetes mellitus. These diabetic cats are often insulin resistants. The dexamethasone suppression test is considered the test of choice for the diagnosis of hyperadrenocorticism. The majority of cats with naturally occurring Cushing’s syndrome have pituitary-dependent hyperadrenocorticism and it is caused by functional microadenoma or macroadenoma pituitary. Computed tomography or magnetic resonance imaging is helpful in diagnosis of pituitary tumors. Treatments of pituitary-dependent hyperadrenocorticism include surgery of the pituitary or adrenals, radiation of the pituitary, and medical therapies. Bilateral adrenalectomy continues to represent the best long-term therapeutic strategy until hypophysectomy becomes more widely available. This paper reports a cat with macroadenoma pituitary causing hiperadrenocorticism and insulin resistance. Case: A 12-year-old female castrated Brazilian shorthair cat was referred to the veterinary due to polyuria, polydipsia, weight loss and polyphagia. The presence of hyperglycemia (blood glucose >250 mg/dl), glucosuria and elevated fructosamine concentration revealed diabetes mellitus. Insulin therapy was introduced but the glycemia was poorly controlled despite the high dose of insulin. Concomitant disease was suspected. Abdominal ultrasonography revealed bilaterally enlarged adrenals. The dexamethasone suppression test showed pituitary-dependent hyperadrenocorticism. Computed tomography or hypophysectomy wasn‘t available. Medical therapy with mitotane was introduced but anorexia and vomiting developed. Bilateral adrenalectomy was performed without complications and histological evaluation of adrenal revealed hyperplasia. After surgery, treatment with mineralcorticoids and glucocorticoids was introduced. The cat had resolution of clinical signs and insulin requirements were decreased. According to the owner, three weeks after surgery, the cat showed abnormal behavior, compulsive walking and circling. The cat died eight months after bilateral adrenalectomy. A complete necropsy was performed and histopathological examination confirmed the pituitary macroadenoma. Discussion: Insulin resistance should be suspected in diabetic cat if control of glycemia is poor despite the high insulin dosage. Clinical signs related to poorly controlled diabetes mellitus are common in cats with hyperadrenocorticism. Hyperadrenocorticism can cause severe insulin resistance and it is often associated with a pituitary macrotumor. Pituitary tumors may lead to hypercotisolism. Bilateral adrenalectomy is a viable alternative to transphenoidal hypophysectomy for treatment of feline pituitary-dependent hyperadrenocorticism when hypophysectomy is not available. Neurological signs can be a result of pituitary tumors and they can get worse after the adrenalectomy because of the enlargement of the tumor. Despite of clinical signs, the cat had improved in response to the bilateral adrenalectomy and had a good quality of life during eight months after surgery.